Influence of technical signature on rowing ergometer performance - Simon, F.; Ertel, G.; Duchene, Y.; Gauchard, G.; Maciejewski, H.; Mornieux, G. (ISBS - Conference Proceedings Archive (Konstanz), 2022)
The purpose of this study was to evaluate the influence of technical signature parameters on rowing ergometer performance defined as power mean handle. 20 high levels rowers were evaluated at their competitive stroke rate on a RowPerfect 3 ergometer. Linear-mixed model analyses revealed that mean power handle was influenced by the power produced by the legs, trunk and arms during the drive phase. The ability to produce the highest relative maximal power throughout the drive phase, whatever its peak value, was important to improve segments powers. Finally, trunk power was enhanced by an earlier peak power of the trunk, and higher trunk and pelvis ranges of motion. These technical elements are important to consider for rowing performance.